Kisah Bung Kecil : Rekam Jejak Sutan Sjahrir 1909 – 1966 - Padiatra, Aditia Muara; Rifal, Rifal; Sanusi, Anwar; Hamidah, Dedeh Nur (IAIN Syekh Nurjati Cirebon, 2023)
As an intellectual as well as an activist for the independence movement, talking about one of the founding fathers of the Republic of Indonesia would certainly be incomplete without discussing the figure of Sutan Sjahrir. The man who was born in Padang Panjang, West Sumatra is known as an accomplished diplomat and was one of the prime ministers during the early period of Indonesian independence. Tracing this matter, it becomes interesting then to be able to see how the side of his life was from time to time, such as childhood and youth, his actions as an independence figure, until the end of his life, this was an effort to then perpetuate the works that what he did, and how then the values that he upheld to become an inspiration for later generations to emulate the figures and figures of Bung Kecil, Sutan Sjahrir's nickname.